POLA Q-MARKETING PERSPEKTIF KOMUNIKASI PEMASARAN THE Q MARKETING PATTERN ON MARKETING COMMUNICATION PERSPECTIVE - Sutamaji .; Sam Abede Pareno; Teguh Dwi Putranto (Universitas Lambung Mangkurat, 2018)
ABSTRACT The rapid growth of digital-based information today, has implications for the need to improvisation and innovation in all areas of life, including business and marketing. Through this reality, in the emerging business world of terms internet marketing, mobile marketing and e-commers. Looking at the problems that, the researchers feel the need to conduct a study of how internet marketing patterns are seen through the perspective of marketing communications. In this study, the researcher examines the new business pattern, which is Q-marketing applied by beauty products company which only two years stand, but succeeded in having a fantastic sales turnover, that is PT Unionfam Azaria Berjaya.Keywords: Q-Marketing, e-Commers, marketing communication. ABSTRAK Semakin pesatnya arus informasi berbasis digital dewasa ini, berimplikasi pada keharusan untuk melakukan improvisasi dan inovasi di segala lini kehidupan, tak terkecuali dunia bisnis dan pemasaran. Melalui realitas inilah, dalam dunia bisnis muncul istilah internet marketing, mobile marketing dan e-commers. Konsep bisnis ini, mengandalkan segala proses pemasarannya melalui dunia digital. Melihat persoalan ini, maka peneliti merasa perlu melakukan kajian tentang bagaimana pola internet marketing ini yang dilihat melalui perspektif komunikasi pemasaran. Pada pembahasan ini, peneliti mengkaji pola bisnis baru, yakni Q-marketing yang diterapkan oleh perusahaan produk kecantikan yang baru dua tahun berdiri, namun berhasil memiliki omset penjualan yang fantastis, yakni PT. Unionfam Azaria Berjaya.Kata Kunci: Q-Marketing, e-Commers, komunikasi pemasaran.